Uterine morphology during diapause and early pregnancy in the tammar wallaby (Macropus eugenii). Issue 3 (11th May 2016) - Laird, Melanie K.; Hearn, Cyrma M.; Shaw, Geoff; Renfree, Marilyn B.
Abstract: In mammals, embryonic diapause, or suspension of embryonic development, occurs when embryos at the blastocyst stage are arrested in growth and metabolism. In the tammar wallaby ( Macropus eugenii ), there are two separate uteri, only one of which becomes gravid with the single conceptus at a post‐partum oestrus, so changes during pregnancy can be compared between the gravid and non‐gravid uterus within the same individual. Maintenance of the viable blastocyst and inhibition of further conceptus growth during diapause in the tammar is completely dependent on the uterine environment. Although the specific endocrine and seasonal signals are well established, much less is known about the cellular changes required to create this environment. Here we present the first detailed study of uterine morphology during diapause and early pregnancy of the tammar wallaby. We combined transmission electron microscopy and light microscopy to describe the histological and ultrastructural changes to luminal and glandular epithelial cells. At entry into diapause after the post‐partum oestrus and formation of the new conceptus, there was an increase in abundance of organelles associated with respiration in the endometrial cells of the newly gravid uterus, particularly in the endoplasmic reticulum and mitochondria, as well as an increase in secretory activity. Organelle changes and active secretion then ceased in these cells as they became quiescent and remained so for the duration of diapause. In contrast, cells of the non‐gravid, post‐partum, contralateral uterus underwent sloughing and remodelling during this time and some organelle changes in glandular epithelial cells continued throughout diapause, suggesting these cells are not completely quiescent during diapause, although no active secretion occurred. These findings demonstrate that diapause, like pregnancy, is under unilateral endocrine control in the tammar, and that preparation for and maintenance of diapause requires substantial changes to uterine endometrial cell ultrastructure and activity.